A study on the effectiveness of the marketing communication of Tru Design Sdn Bhd. / Wan Noor Azizah Wan Ismail - Wan Ismail, Wan Noor Azizah (1993)
Tru Design Sdn Bhd specialized in the design of promotional items. It seems to be that promotion is a heartbeat in this business; without promotion it's like trying to fill a leaky bucket with water. Due to this, the leakage seems to occur to* the company when existing customers order less, are lost to competitors, go out of business or fail ti? reorder. The promotional items company in Malaysia is a growing industry. There are a great potential for this industry to expand. The companies have to be on their toes all the time in order to be able to compete successfully in the industry. Each of the company must have a competitive edge over the other. One of the ways that they could have an edge over the other is to have a complete and favorable image of the company; that is potrayed to their respective clients. Currently, Tru design Sdn Bhd seems lacking of promotion and the degree of awareness to the client is low. The objective of this report is to recommend that Tru Design Sdn Bhd should undertake suitable promotion programmes in order to achieve the effectiveness of the marketing communication. Information are gathered and analysed. They are obtained through the secondary data and primary data collection methods. A small survey was done to find out the perception of the employees and the respective clients towards the degree of promotion, awareness about the company and the effectiveness of the marketing communication. Finally, the results of the survey were analyzed and presented in the form that is easily understood. Then recommendations were made in view of the findings and these recommendations were based on the marketing communications activities that the company should embark in. It is hoped that the recommendations suggested, will provide Tru Design Sdn Bhd with an effecient method of projecting the favorable degree of awareness that they would like to potray to their respective clients and will achieve the effectiveness in the marketing communication.